ANALISIS MIDDLE-INCOME TRAP DI INDONESIA - Aprisal W. Malale; Maung Agus Sutikno (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2014)
Indonesia is predicted to be one of driving force for world economic growth in couple decades ahead. Now, Indonesia is still classified as middle income country and on the way to be a high income country. But, there is a risk not being able to inline in trajectory of economic growth. This study aims to find out about the middle income Trap (MIT) in indonesia, by answering the most fundamental question whether Indonesia has entered into MT, and what macroeconomic factors influence GNI per kapita as the income category. Using data published by the world bank, and multiple regression analysis, it showed that indonesia has entered the MIT trap. In addition, based on the results and analysis, it can be concluded that the variables exports of goods and services, value added agriculture , as well as aid and foreign assistance (with lag or no lag ) Significantly give negative effect on GNI percapita. Gross Capital Formation variables significantly give positive effect ( In current year) and negative affect (at 2 and 3 Year earlier) to GNP percapita in current year. Inflation variable gives no significant effect on GNI percapita. Government are recommended to take policy by focusing on improving the productivity of indonesia to encourage the growth of knowledge-based economy and more equitable distribution of targeted welfare.